Exploring Video Content Creation Strategies to Enhance Unipdu Brand Awareness: A Qualitative Approach - Maisarah, Maisarah; Herjanti Nursuksmaningtyas Santoso (Indonesian Journal of Advanced Research, 2024)
Brand awareness serves as a crucial factor in setting apart educational institutions amidst competition and enticing potential stakeholders. Utilizing video content emerges as an effective avenue for conveying a university's ethos and values, thereby enriching brand recognition. This study endeavors to explore impactful strategies in video content creation aimed at fortifying the brand awareness of Universitas Pesantren Tinggi Darul Ulum (Unipdu). Employing a qualitative methodology, the research employs in-depth interviews, focus group discussions, and content analysis to glean insights from Unipdu stakeholders. Through thematic analysis, recurring patterns and themes concerning effective video content strategies for brand awareness are delineated. The findings unveil Unipdu's alignment with branding theory, accentuating the emphasis on brand identity development, strategic positioning, and the cultivation of brand equity. Concurrently, content marketing strategies, tailored to each stage of the buyer's journey, are implemented to effectively engage prospective students. In conclusion, Unipdu's concerted efforts in strategic branding and content marketing, underpinned by theoretical frameworks, have propelled the university to the forefront of the education sector. By harmonizing content strategies with audience requisites and assessing effectiveness, Unipdu not only bolsters its brand perception but also beckons stakeholders, thereby fortifying its competitive edge.